INNOVATION-DRIVEN ENTREPRENEURSHIP IN EMERGING ECONOMIES: CHALLENGES AND POLICY PERSPECTIVES (Eureka Journal of Business, Economics & Innovation Studies, 2025)
Innovation-driven entrepreneurship plays a pivotal role in transforming emerging economies from resource-based to knowledge-based systems. This study investigates the drivers, barriers, and policy mechanisms that shape innovation-oriented entrepreneurial ecosystems in developing countries. Using secondary data and comparative analysis, the research identifies how innovation capital, digital infrastructure, and policy support influence entrepreneurial success. The findings suggest that while innovation ecosystems in emerging economies have matured significantly since 2015, structural challenges such as financing gaps, institutional weaknesses, and inadequate research–industry linkages persist. The paper concludes with a set of actionable policy recommendations to enhance innovation-driven entrepreneurship as a key pillar for sustainable economic growth.
Keywords: INNOVATION-DRIVEN ENTREPRENEURSHIP IN EMERGING ECONOMIES: CHALLENGES AND POLICY PERSPECTIVES